2010
DOI: 10.1007/s00540-009-0855-z
|View full text |Cite
|
Sign up to set email alerts
|

Compressing the non-dependent lung during one-lung ventilation improves arterial oxygenation, but impairs systemic oxygen delivery by decreasing cardiac output

Abstract: Although non-dependent lung compression may be a potentially effective measure to treat hypoxemia during OLV, it should be noted that CO and systemic oxygen delivery may be decreased by this maneuver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 22 publications
0
14
1
1
Order By: Relevance
“…The most likely explanation for changes in arterial oxygenation after compression of the nondependent lung is the diversion of blood flow to the dependent lung by physical compression and kinking of the lung vessels. However, our recent follow-up study using a minimally invasive CO monitor suggested that nondependent lung compression reduced DO 2 despite improvement in arterial oxygen saturation [12]. Because the decrease in DO 2 was mainly caused by the reduction of CO associated with the compression of the nondependent lung [12], we aimed to maintain CO without compromising arterial oxygenation in the present study.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…The most likely explanation for changes in arterial oxygenation after compression of the nondependent lung is the diversion of blood flow to the dependent lung by physical compression and kinking of the lung vessels. However, our recent follow-up study using a minimally invasive CO monitor suggested that nondependent lung compression reduced DO 2 despite improvement in arterial oxygen saturation [12]. Because the decrease in DO 2 was mainly caused by the reduction of CO associated with the compression of the nondependent lung [12], we aimed to maintain CO without compromising arterial oxygenation in the present study.…”
Section: Discussionmentioning
confidence: 93%
“…However, our recent follow-up study using a minimally invasive CO monitor suggested that nondependent lung compression reduced DO 2 despite improvement in arterial oxygen saturation [12]. Because the decrease in DO 2 was mainly caused by the reduction of CO associated with the compression of the nondependent lung [12], we aimed to maintain CO without compromising arterial oxygenation in the present study. Ephedrine was selected as an inotropic agent because it anecdotally had been found to be effective in case of hypotension during lung retractor application in our institution, but also because of its favorable pharmacodynamic and safety profile.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations